A dynamic model for process flowsheet simulation of semi-batch precipitation of sparingly soluble salts. (9th June 2020) - Rehage, Hendrik; Semmel, Malte; Kind, Matthias
Abstract: Semi-batch precipitation of sparingly soluble materials is an important unit operation in the chemical or pharmaceutical industry. Unfortunately, dynamic process flowsheet simulation of this unit operation has not been possible yet, as existing models for stirred-tank reactors are far too computationally intensive. In this work, we present a real-time capable semi-batch model for precipitation process flowsheet simulation. Its outstanding numerical performance is based on a frequently triggered approximation of the steady-state reaction zone in the tank. We validate the model by barium sulfate precipitation experiments and investigate the semi-batch specific process dynamics. Furthermore, the model is applied to simulation setups with dynamic boundaries and process parameters to characterize the influence of dynamic process parameters on the product particle size distribution (PSD). It is shown that dynamic process parameters can influence the final PSD heavily. The model will, therefore, be a useful tool for future application in dynamic process optimization.